STUDY ON AlUNINA SILICO-PHOSPHATE COMPOUND AS WATER TREATMENT: CASE STUDY GROUND WATER PANTURA (BEKASI AND KARAWANG) - Dewi Fatimah (Jurnal Zeolit Indonesia, 2004)
Naturally, zeolite is a cation exchanger but this property is also depending on porosity, tetrahedral density and frame density. Cation exchange effectiveness can be changed by structure, Si/Al ratio and effective pore size. Tetrahedral group, T, in zeolite is negative charged and can be substituted isomorphycally by other group like PO2+. The new structure can be functioned as anion or cation exchanger. The exchange capacity of both ions depends on Si/Al/P ratio from the substitution process. The alumina-silicaphosphate (ASP) compound has been made from zeolite from Cikalong, Tasikmalaya, with ammonium dihydrogen phosphate (ADHP) with substitution rate between 30-40%. This product has been tested to Pantura groundwater, in Bekasi and Karawang areas,which have groundwater type of NaCl, CaCl2, MgSO4 and CaCl2/CaSO4. ASP tests on ground water samples show decreasing content of Ca, Mg, Na and K cations in ground water by 32.94%, 3.35%, 2.52% and 23.60% respectively. Sulphate anion also decreases by 15.39% but chloride anion shows no changes. Dig-up well of CaCl2 type also shows a reduction of Ca, Mg, Na and sulphate contents by 46.26%, 18.37%, 16.39% and 10.84%, respectively. Dig-up well of CaSO4 type shows Ca, K and sulphate contents decrease of 89.71%, 33.31% and 5.26%, respectively. CaSO4 dig-up well can be changed to Mg-mix type after processing by ASP compound. Cation exchange capacity of ASP compound to Ca is higher than to K, Mg and Na (Ca>K>Mg>Na). Due to a high cation exchange capacity to K and Mg, ASP compound may be used to reduce the hard water level.